Saber fazer : a circulação de informação entre comunidades marítimas no início dos tempos modernos - Barros, Amândio Jorge Morais (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
In this essay I'll intend to analyse some aspects of the knowledge diffusion amid Portuguese and European maritime centres between late Middle Ages and Early Modern Times. The starting point will be the identification of maritime societies. Who are those members and how each one of them acted adding new outlooks in the subject? As we all recognize the 14th century has been a period of intense international bonds involving the major European costal zones: a period of development of enlarged maritime networks alongside with market enlargement and vital economic connections. Here we can find the origins of an enlarged maritime heritage which will be patent in times ahead, namely in the 16th century Europe. In that way, we must try to define "maritime cultures" and articulated economic centres: from the Baltic to the Mediterranean, merchants and sailors find out how people deal with common problems in different areas: how to build a ship set to sail in a particular surrounding; how the seaports were planned and arranged; the rules and ways of commerce; the mentalities that were displayed by the men who lived from what the Sea provided. These are some of the basics of interaction and maritime cultural diffusion in this extended area. The first part of the study, which is a foremost of a long term research project, will be dedicated to commercial techniques: how European merchants acquire privileged information about the ways of the trade. On the second part I'll look after shipyard procedure: how carpenters, caulkers, rope makers and other specialized workers developed solutions in order to build new and increasingly successful ships. Throughout this text the circulation of people all over European maritime centres observing, writing about ports, trades, and ships, and communicating what they saw to their fellowship will the emphasised. Circulation of people means information diffusion. These are the Modern Times at its best.